Prospero i Kurz w lustrze pamięci: Przeniesione pozycje sprawcy, ofiary i świadka w polskim dyskursie publicznym drugiej dekady XXI wieku (Politeja, 2015)
Prospero and Kurz in the Mirror of MemoryIn this article – based on selected examples and with no certainty that they have been aptly chosen – I would like to point out and make a preliminary analysis of certain positions in Polish public discourse which currently display striking elements of transference in the sense of Dominick LaCapra’s meaning of the term. They reverberate with reflections of Polish imagined community’s experiences from the Occupation period. In this description, I shall rely on the classic categorisation introduced by Raul Hilberg, successively discussing the identification of subjects with the positions of perpetrator, victim and witness.